Binding affinity of synthetic cannabinoids to human serum albumin by high-performance affinity chromatography - Santos, Rita M. G.; Cravo, Sara; Remião, Fernando; Fernandes, Carla (Scientific Letters, 2024)
Background: The use of new psychoactive substances (NPS) has been growing since the 2000’s, being the synthetic cannabinoids one of the groups reported on a larger scale. This group of NPS primarily interacts with the endocannabinoid system, which is involved in many physiological functions. Numerous reports of severe morbidity and mortality, linked to their consumption, have been documented [1,2]. Studies of toxicodynamics and toxicokinetics of synthetic cannabinoids are pivotal to increase the knowledge of this class of NPS. To our knowledge, studies of the interaction of synthetic cannabinoids with human serum albumin (HSA), the most abundant plasma protein, are still very limited [3]. Objective: This work aims the evaluation of binding affinity of a series of synthetic cannabinoids by high-performance affinity chromatography (HPAC). HPAC is a widely used and efficient technique to study intermolecular interactions between HSA and drugs [4,5]. Methods: The interaction of synthetic cannabinoids with HSA was investigated by HPAC by zonal elution experiments for measuring the retention times of each cannabinoid on an HSA column. Mixtures of potassium phosphate buffer (67 mM, pH 7.0) and acetonitrile were used as mobile phases in reversed elution mode. Results: The binding percentages (%b) values ranged from 94 to 99%. ADB-FUBINACA and AMB-FUBINACA (MMB-FUBINACA) showed the highest binding affinity both with a %b of 99%. Conclusions: The synthetic cannabinoids bounded to HSA with high affinity, which can interfere with drugs pharmacokinetics by increasing their free fraction in blood, as result of their eventual displacement from albumin or even by saturation of this protein. Zonal displacement chromatography studies are being conducted, using competitors with known specific binding sites on HSA, such as warfarin and (S)-ibuprofen, to shed light on the sites where the selected cannabinoids bind to the protein.